The Role Of Financial Factor On The Financial Behaviour Of Small And Medium Enterprises (SMEs) - Anita handayani (Journal of Business and Management Review, 2023)
Small, and Medium Enterprises (SMEs) play an essential role in economic growth and development in Indonesia. SMEs are an integral part of the national business world, which has a strategic position, potential, and role in realizing national development goals. So to achieve the above objectives, it is necessary to have SMEs that can survive in various conditions. Good management is needed to manage these SMEs, one of which is the financial behavior of SMEs because financial behavior is an individual's perception of controlling the source of funds (money). So, good financial behavior needs to be owned by SMEs to maintain the continuity of their business. This study aims to analyze the role of financial factors that can influence the financial behavior of SMEs. The financial factors used in this study are Financial Literacy, Financial Attitude, and Locus of Control. This study used 150 SMEs at religious tourism sites in Gresik City. The results of the study show that all financial factors can be factors that can have an impact on the financial behavior of SMEs